Faktor-Faktor Penghambat Anak dalam Akses Pendidikan: Studi Kasus pada Keluarga Anak Jalanan - Hilda Haerany Arsyad; Haerani Nur (Scidacplus, 2026)
Street children face educational barriers due to socioeconomic pressures, despite parents' positive views of education. This study aims to identify factors inhibiting street children's education, describe parents' efforts to send their children to school, and understand their expectations of sending their children to school. A qualitative approach was applied through a case study design in two street children's families in Makassar City. Data were collected through in-depth interviews and observations, and analyzed following Creswell's data analysis stages. The results show that educational barriers are divided into two categories: internal barriers in the form of low motivation and interest in learning, while external barriers include family factors, economic factors, distance and access to school, the environment and peers, and the pandemic. Despite these obstacles, parents continue to strive for their children's education through hard work, motivation, adaptation to limitations, communication with schools, and seeking help and support. Parents do this because they hope for a better future for their children, and children will avoid social risks, character development, social capital, and improved family conditions. The implications of this study emphasize the need for policies that are more responsive to the conditions of street children and a more flexible and empathetic learning approach.